Repositioning MPI within the Islamic Higher Education Landscape: Strategic Policies and Curriculum Responsiveness for Graduate Employability - Ismail, Iqbal Maulana (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2025)
This study explores the repositioning of the Islamic Education Management (MPI) study program within the landscape of Islamic Higher Education Institutions (PTKI), through a strategic review of national policies and curriculum responsiveness to labor market demands. This study aims to provide strategic recommendations for aligning MPI curricula and quality management practices with labor market needs in order to enhance graduate employability. Despite the MPI curriculum having been developed based on the Indonesian National Qualification Framework (KKNI) and Learning Outcomes (CPL), tracer studies consistently show low graduate absorption in relevant managerial and educational roles. At the same time, DIKTIS policies, such as the PTKI Curriculum Guide and KMA No. 347/2022, provide normative directions for quality improvement but are hindered by structural and cultural barriers at the program level. This study employs a literature review and institutional policy analysis using official documents and empirical data from several PTKIN campuses. The findings indicate the need to shift from an administrative approach toward outcome-based quality management and intersectoral collaboration. Repositioning MPI requires adaptive curricula, strong engagement with industry, and a more strategic role for DIKTIS as a policy facilitator.